(untitled) (REMUNOM, 2024)
Introduction: The therapeutic approach to mental disorders has undergone significant changes over time. Currently, mental health care has a more humanized perspective, involving the family and the community, but the therapeutic process is still permeated by challenges. Pharmacists play a broad role in the treatment of mental disorders, ranging from pharmacotherapeutic monitoring to educational actions aimed at patients and their families. Objective: to analyze the role of pharmacists in guiding patients and caregivers in mental health, through an integrative literature review. Method: integrative literature review. The studies were located in electronic databases with free access on the internet. Only studies published between 2019 and 2023, covering a period of 5 (five) years, were selected; publications in Portuguese or English, and having in the title or abstract at least one of the descriptors used in the search criteria. Studies that diverged from the inclusion criteria, as well as monographs, dissertations and other course completion works, were not selected. Results and discussion: only 12 studies met the eligibility criteria. The synthesis of the studies showed that pharmacists have played an important role in counseling patients and caregivers, contributing to greater adherence to treatment, active patient participation, reduced burden on caregivers, encouraging self-care, and better results from the therapy instituted. Pharmacists have expanded their skills in the field of mental health care, achieving greater professional recognition through an educational approach and humanized care. Conclusion: the role of pharmacists in caring for users with mental disorders is not limited to counseling on drug treatment, but reaches a deeper dimension of care, taking into account the needs of patients and the importance of involving caregivers.